TA’LIM SAMARADORLIGINI OSHIRISHDA MASALALARNING O‘RNI - Babayeva М.А. (SCIENCE and SOCIETY, 2024)
In the process of solving problems are formed along with instilling knowledge in schoolchildren, independence, initiative, cooperation, honest assessment, creative thinking, the ability to distinguish information and its rational use, rapid accessibility, as well as the ability to constructively adapt to any changes.